Peer Teaching sebagai Metode Pembelajaran untuk Meningkatkan Hasil Belajar Pembuatan Busana Industri - Jayaul Khoiriyah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2021)
The research objective is to improve activities and result learning industrial clothing manufacturing subject through peer teaching learning method. The research method used was Classroom Action Research (CAR). The research subject was 31 students of class XI dressmaking A SMK Negeri 2 Gedangsari in the 2019/ 2020 school year. Data were analyzed using quantitative and decriptive qualitative techniques. The result of the research is that peer teaching learning method can improve activities and industrial clothing manufacturing subject outcomes. The increase in students activities is indicated from pre-cycle, cycle I and cycle II. In the pre-cycle stage, 1) there are 6 (19,35%) increase become 14 (45,16%) who actively ask question, 2) there are 5 (16,12%) increase become 15 (48,38%), who actively answer the question. 3) There are 4 (12,90%) become 15 (48,38%) who actively work together, 4) There are 5 (16,12%) become 20 (64,51%) who actively do the assignments, in the end of cycle. While the increase of industrial clothing manufacturing subject outcomes is indicated by the increase in the presentage of the number of students whose grades reach KKM from pre-cycle, cycle I and cycle II. In the pre-cycle stage, there are 7 students (22,58%) whose grades reach the KKM. In cycle I, there are 17 students (54,83%), in the second cycle, there are 26 students (84%).